(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3GdHhe hJfJ QjMg EPkG JedC faSg ef CeddgG hcag ef LeYgG ai GdeSGA s
(3BNQgG (B:s
(3hGdYSd gh ZQhQ GdfGS ai GdOfjG JYdjd eG jfGdhfg ajgG ef dPI GdYjT CfG UGMHc GdPi dGjNPdc bGHd CfaS GdadGSaI Ke bVi eG Je Pdc HYhf Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs